Type D Personality Is an Independent Predictor of Lower Urinary Tract Symptoms in Young Men - Cheng, Wei-Ming; Liou, Ying-Jay; Fan, Yu-Hua (Frontiers in Psychology, 2022)
This cross-sectional study, which included men aged 20–40 years, aimed to determine the relationships among type D personality, depressive symptoms and lower urinary tract symptoms in young men. An internet-based questionnaire was administered, and General demographics, International Prostate Symptom Scores, Type D Scale-14 scores, and Depression and Somatic Symptom Scale scores were analyzed. A total of 3,127 men were included; of these, 762 (24.4%) reported moderate/severe lower urinary tract symptoms, and 1,565 (50.05%) met the criteria for type D personality. Men with type D personality had significantly higher body mass index and total and sub-scores for the International Prostate Symptom Score and Depression and Somatic Symptom Scale. Furthermore, the type D personality group had a higher prevalence of lower urinary tract symptoms, particularly voiding symptoms. Univariate analysis revealed that all parameters, except for body mass index, were significant predictors of moderate/severe lower urinary tract symptoms. Multivariate analysis showed that age > 30 years, type D personality, and depressive and somatic Depression and Somatic Symptom Scale sub-scores were independent predictors of moderate/severe lower urinary tract symptoms. Regarding Type D Scale-14 subscales, social inhibition, rather than negative affectivity, impacted moderate/severe lower urinary tract symptoms. Mediation analysis revealed that depressive symptoms mediated the relationship between type D personality and lower urinary tract symptoms. This study established correlations between type D personality, depressive symptoms, and lower urinary tract symptoms. As previous studies suggested that patients with type D personality are less likely to consult and adhere to treatment, and are at higher risk for depression, urologists should therefore actively recognize patients with TDP.